TINJAUAN YURIDIS TERHADAP HAK WARIS ISTRI DALAM PERKAWINAN SIRI PADA MASYARAKAT ADAT ACEH DI KECAMATAN DARUL IMARAH MUKIM DAROY/JEUMPET DESA GAROT KABUPATEN ACEH BESAR PROVINSI ACEH - M. REZZA SEPTHIO (PREMISE LAW JURNAL, 2015)
Aceh adat community constitutes basic culture in Islamic law, including unregistered marriage which is know by Acehnese Moslems in Aceh because of the development of Islam in Aceh so that marriage is always related to Islamic Fiqh. In Aceh adat, unregistered marriage is valid in the Islamic law although the process is ot before PPN (marriage clerk) in Subdistrict Religious Affairs Office. In thiscase, there is no dichotomy abaout the validity of the marriage between the Islamic law and Law No. 1/1974 in Marriage and between the Islamic law and KHI (Compilation of Islamic Law) as the positive law in Indonesia. Therefore, a valid marriage is a marriage which has fulfilled all requirements without any obstacles.In the Aceh adat, the position of woman who performs an unregistered marriage according to the Islamic Fiqh is equal to woman who has registered marriage. Keywords: Inheritance Rights, Unregistered Marriage, Aceh Adat Community